Aggregate Planning to Minimize Cost of Production in Manufacturing Company - Noegraheni, Enny; Nuradli, Hasbi (Bina Nusantara University, 2016)
The rapid growth of seafood industry has lead to fierce competition. PT Anela is one of the major players in its industry. The company needs to develop a good strategy for competitive advantage in winning the competition. PT Anela is one of the ma jor players in the seafood industry. However, they have limitation in production capacity. The objectives of this study are to calculate the forecast demand and to develop aggregate production planning for PT Anela to meet demand with the lowest cost. The data is gathered through literature review and secondary data gathered directly from the company itself. The demand data from past three years was used to forecast demand using linear regression with seasonal index. Furthermore, all data was analyzed and used to design aggregate planning by using three strategies namely Chase, Level and Mixed strategy which calculated by POM for Windows. The results of this study show that the mixed strategy is the optimal strategy .